2017
DOI: 10.3389/fmicb.2017.00143
|View full text |Cite
|
Sign up to set email alerts
|

Compositions and Abundances of Sulfate-Reducing and Sulfur-Oxidizing Microorganisms in Water-Flooded Petroleum Reservoirs with Different Temperatures in China

Abstract: Sulfate-reducing bacteria (SRB) have been studied extensively in the petroleum industry due to their role in corrosion, but very little is known about sulfur-oxidizing bacteria (SOB), which drive the oxidization of sulfur-compounds produced by the activity of SRB in petroleum reservoirs. Here, we surveyed the community structure, diversity and abundance of SRB and SOB simultaneously based on 16S rRNA, dsrB and soxB gene sequencing, and quantitative PCR analyses, respectively in petroleum reservoirs with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 66 publications
4
45
2
1
Order By: Relevance
“…Clostridia was the second most abundant class in the majority of corrosion samples. This was similar observation to the results of a study of the composition of the bacterial community composition of biofilms from metal surfaces of an alkaline district heating system, and samples collected from water-flooded petroleum reservoirs ( Kjeldsen et al, 2007 ; Tian et al, 2017 ). Some important SRB groups also belong to this class, for instance Desulfotomaculum .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Clostridia was the second most abundant class in the majority of corrosion samples. This was similar observation to the results of a study of the composition of the bacterial community composition of biofilms from metal surfaces of an alkaline district heating system, and samples collected from water-flooded petroleum reservoirs ( Kjeldsen et al, 2007 ; Tian et al, 2017 ). Some important SRB groups also belong to this class, for instance Desulfotomaculum .…”
Section: Discussionsupporting
confidence: 87%
“…At the class level, Deltaproteobacteria was the dominant class in the majority of corrosion samples. This observation parallels information from studies of the bacterial communities of samples collected from water-flooded petroleum reservoirs, water injection systems of Brazilian offshore oil platforms, and corrosive petroleum reservoirs in Yangzhou ( Korenblum et al, 2010 ; Li et al, 2016 ; Tian et al, 2017 ). There are many important SRB groups belonging to this class, e.g., Desulfovibrio , Desulfobacter and Desulfonatronum .…”
Section: Discussionsupporting
confidence: 73%
“…Today, we do not have any elements, in terms of physico‐chemical or geological data, likely to explain this diversity. This SRM association ( Desulfobacteraceae , Desulfobulbaceae , Desulfomicrobiaceae , Desulfovibrionaceae , Peptococcaceae ) have already been found from water‐flooded petroleum reservoirs (Tian et al ., ). It should be noted that members of the Desulfovibrionaceae, Desulfobacteraceae, Desulfomicrobiaceae and Desulfobulbaceae families are often associated with degradation of aromatic and polyaromatic hydrocarbons in aquifers, contaminants which are present in natural gas (Ramos et al ., ; KĂŒmmel et al ., ; Daghio et al ., ; Pilloni et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, in the initial wellhead fluid, we also observed a high proportion of Deltaproteobacteria. Although they often occurred in production water of high temperature oil reservoirs ( Guan et al, 2013 ; Li et al, 2016 ; Tian et al, 2017 ), it is also possible that they might come from cool portions of the wellbores not the deep oil reservoirs. And it has been reported that the wellhead samples of high-temperature, low-permeability petroleum reservoirs could represent the communities inhabiting the wellbores, instead of the reservoirs ( Song et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%